On the path towards european union's sustainable urban mobility plans: solving Turkey's urban mobility problems - Yerli, Bilgesu Güneş (My University, 2017)
2000 lerden itibaren kentleşmenin etkisiyle dünyadaki büyük şehirlerde, vatandaşların hayat kalitesi giderek azalmaktadır. ABSTRACT The life quality of citizens is diminishing with the urbanisation since 2000s in all major cities around the world.
Keywords: 21. yy; AB; Bisiklet; Cycling; EU; Gösterge SUMP; Hareketlilik; Indicator; Kentler; Kentleşme; Mobility; Sorunlar; Sosyal hareketlilik; SUMP; Sustainable; Sürdürülebilir; Transport; Turkey; Türkiye; Ulaşım